(Retracted) The Effectiveness of Adventure Based Counseling Program to Improve Student Happiness - Setyowati, Aprilia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2018)
The purpose of this study was to determine the effectiveness of Adventure Based Counseling program to increase student happiness. Results to be achieved is the increasing level of happiness student. Happiness is a positive emotion in order to achieve significance in the life of each individual. Each individual strives to achieve happiness by the role and environmental conditions. Individuals who have happiness tend to produce things that are positive in the personal-social aspects, learning, and career. Research conducted using an experimental model design with one group pretest-posttest. The research subjects are students of class III D4 Semester Study Program Guidance and Counseling UAD selected with purposive sampling technique. Data is collected using questionnaires and interviews. The data obtained and analyzed by non-parametric data analysis with Test Wilxocon. The results obtained by analysis meaning significant value 0.798> 0.05, adventure-based counseling program administration no significant effect on student happiness. However, there is the influence of adventure-based counseling services before and after treatments are mainly on the aspect of significance and accomplishment. This is evident from the change in happiness scores of students before and after treatments.